2013
DOI: 10.1063/1.4830115
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and mixture profiles in dense, inclined flows of two types of spheres

Abstract: We study dry flows of two types of spheres down an inclined, rigid, bumpy bed in the absence of sidewalls. The flow is assumed to be steady and uniform in all but the direction normal to the free surface, collisions between particles are dissipative, and the sizes and masses of the particles are not too different. We restrict our analysis to dense flows and use an extension of kinetic theory to predict the concentration of the mixture and the profile of mixture velocity. A kinetic theory for a binary mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 36 publications
4
64
0
1
Order By: Relevance
“…However, it is not yet clear that it can fully explain the rise of large particles to the surface of an avalanche in chute flow [75], where high granular temperatures develop near the base of the flow [64] rather than at the surface. If the kinetic stresses do turn 100 out to be the critical driving forces for segregation then it will be necessary to compute them as part of the solution for the bulk flow [76], which significantly complicates the model.…”
Section: Segregation Flux Functionsmentioning
confidence: 99%
“…However, it is not yet clear that it can fully explain the rise of large particles to the surface of an avalanche in chute flow [75], where high granular temperatures develop near the base of the flow [64] rather than at the surface. If the kinetic stresses do turn 100 out to be the critical driving forces for segregation then it will be necessary to compute them as part of the solution for the bulk flow [76], which significantly complicates the model.…”
Section: Segregation Flux Functionsmentioning
confidence: 99%
“…However, it is not yet clear that it can fully explain the rise of large particles to the surface of an avalanche in chute flow [75], where high granular temperatures develop near the base of the flow [64] rather than at the surface. If the kinetic stresses do turn out to be the critical driving forces for segregation then it will be necessary to compute them as part of the solution for the bulk flow [76], which significantly complicates the model. Gray and Ancey [44] showed that it is possible to generalize the bidisperse model to any number of discrete grain-size classes.…”
Section: Segregation Flux Functionsmentioning
confidence: 99%
“…J.M.N.T. Gray et al / C. R. Physique 16 (2015) [73][74][75][76][77][78][79][80][81][82][83][84][85] jacente de grains statiques ou en déplacement lent. La combinaison de la ségrégation et des changements de phase solide-fluide granulaire crée des motifs complexes dans les dépôts résultants, mais la compréhension complète de ces effets est pour le moment hors de portée.…”
unclassified
“…Recently Larcher & Jenkins (2013) extended kinetic theory to predict segregation of binary granular mixtures in dense flow and obtained qualitative agreement with discrete element method (DEM) simulations, but a first-principles based theory capable of quantitatively predicting segregation for dense flow is still lacking. In the meantime, a broad theoretical framework for segregation-driven pattern formation in dense flows is emerging (Gray & Thornton 2005;Gray & Chugunov 2006;Thornton et al 2006;May et al 2010;Wiederseiner et al 2011;Marks et al 2011;Thornton et al 2012;Kowalski & McElwaine 2013).…”
Section: Introductionmentioning
confidence: 99%